Spatial but not temporal orienting of attention enhances the temporal acuity of human peripheral vision - Francois R. Foerster; A. Giersch; A. Cleeremans (Communications Psychology)
Abstract The temporal acuity of a sensory system determines its capacity to detect delays between events, which enables following events in time and adapting behaviors accordingly. Whether and how voluntary attention drives visual temporal acuity is still unclear, especially in peripheral vision where attention is critical to avoid missing information. The present study aims at 1) evaluating whether cue-based spatial and temporal orientation of visual attention modulates the temporal acuity in peripheral vision, 2) assessing to what extent these modulations rely on shared or distinct attentional mechanisms, and 3) exploring whether these modulations are cumulative or independent from each other. Forty participants performed an asynchrony detection task in immersive virtual reality whilst electroencephalographic and pupillary dynamics were recorded. We found reductions of pupil constriction during the processing of attentional cues, suggesting that the pupil diameter represents a readout of the formation of spatiotemporal expectations. We further found that pre-target oscillatory dynamics in posterior theta and alpha bands are suppressed by both spatial and temporal orienting of attention, with cumulative effects, thus providing evidence for integrated mechanisms of spatial and temporal attention. Yet, despite these modulations, only explicit spatial orienting enhances the sensitivity to asynchronies. This highlights that explicit endogenous attention directed to space—but not to time—increases the temporal acuity under spatial uncertainty in peripheral vision. Overall, these results cast unambiguous doubts on the accepted trade-off that spatial attention meliorates spatial visual acuity while impeding temporal visual acuity, and thus call for the further refinement of models of visual attention.